Influence of brand loyalty on consumer sportswear - Wong, Foong Yee (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
The purpose of this research is to investigate how the respondents are influenced by factors of brand loyalty towards sportswear brands. Previous research adopted seven factors to test in the Malaysian environment. The seven factors of brand loyalty are brand name, product quality, price, style, promotion, service quality and store environment. Brand name has shown strong correlation with brand loyalty. In order to increase customer satisfaction and drive them to be brand loyalists, marketers are encouraged to develop aggressive marketing programs. Questionnaires were distributed and self-administered to 100 respondents. Descriptive analysis, one-way ANOVA and Pearson Correlation were used in this study. The research results showed that there is positive and significant relationship between factors of brand loyalty (brand name, product quality, price, style, promotion, service quality and store environment) with sportswear brand loyalty. Study of more focused factors that are appropriate to the Malaysian environment is recommended in order to obtain accurate information.